Rapid prenatal diagnosis using targeted exome sequencing: a cohort study to assess feasibility and potential impact on prenatal counseling and pregnancy management. (November 2018) - Chandler, Natalie; Best, Sunayna; Hayward, Jane; Faravelli, Francesca; Mansour, Sahar; Kivuva, Emma; Tapon, Dagmar; Male, Alison; DeVile, Catherine; Chitty, Lyn
Abstract Purpose Unexpected fetal abnormalities occur in 2–5% of pregnancies. While traditional cytogenetic and microarray approaches achieve diagnosis in around 40% of cases, lack of diagnosis in others impedes parental counseling, informed decision making, and pregnancy management. Postnatally exome sequencing yields high diagnostic rates, but relies on careful phenotyping to interpret genotype results. Here we used a multidisciplinary approach to explore the utility of rapid fetal exome sequencing for prenatal diagnosis using skeletal dysplasias as an exemplar. Methods Parents in pregnancies undergoing invasive testing because of sonographic fetal abnormalities, where multidisciplinary review considered skeletal dysplasia a likely etiology, were consented for exome trio sequencing (both parents and fetus). Variant interpretation focused on a virtual panel of 240 genes known to cause skeletal dysplasias. Results Definitive molecular diagnosis was made in 13/16 (81%) cases. In some cases, fetal ultrasound findings alone were of sufficient severity for parents to opt for termination. In others, molecular diagnosis informed accurate prediction of outcome, improved parental counseling, and enabled parents to terminate or continue the pregnancy with certainty. Conclusion Trio sequencing with expert multidisciplinary review for case selection and data interpretation yields timely, high diagnostic rates in fetuses presenting with unexpected skeletal abnormalities. This improves parental counseling and pregnancy management.